Comparative Transcriptomic Analysis of Streptococcus thermophilus TH1436 and TH1477 Showing Different Capability in the Use of Galactose - Giaretta, Sabrina; Treu, Laura; Vendramin, Veronica; da Silva Duarte, Vinícius; Tarrah, Armin; Campanaro, Stefano; Corich, Viviana; Giacomini, Alessio (Frontiers in Microbiology, 2018)
Streptococcus thermophilus is a species widely used in the dairy industry for its capability to rapidly ferment lactose and lower the pH. The capability to use galactose produced from lactose hydrolysis is strain dependent and most of commercial S. thermophilus strains are galactose-negative (Gal−), although galactose-positive (Gal+) would be more technologically advantageous because this feature could provide additional metabolic products and prevent galactose accumulation in foods. In this study, a next generation sequencing transcriptome approach was used to compare for the first time a Gal+ and a Gal− strain to characterize their whole metabolism and shed light on their different properties, metabolic performance and gene regulation. Transcriptome analysis revealed that all genes of the gal operon were expressed very differently in Gal+ and in the Gal− strains. The expression of several genes involved in mixed acid fermentation, PTS sugars transporter and stress response were found enhanced in Gal+. Conversely, genes related to amino acids, proteins metabolism and CRISPR associated proteins were under-expressed. In addition, the strains showed a diverse series of predicted genes controlled by the transcriptional factor catabolite control protein A (CcpA). Overall, transcriptomic analysis suggests that the Gal+ strain underwent a metabolic remodeling to cope with the changed environmental conditions.